Corporate Social Responsibility and Poor’s Child Well Being in Developing Customer’s Loyalty PDF - Mukhtar, Syahrial; Daryanti, Sri; Khairani, Khairani (UI Scholars Hub, 2021)
This research was conducted to analyze the contribution of Corporate Social Responsibility (CSR) perceived motives in enhancing poor children's well being and consumer loyalty. CSR strategy studied were CSR strategies implemented by two companies, Garuda Indonesia and Pertamina, which are State Owned Companies (fully or partially owned by government of Indonesia). Garuda Indonesia is a service company engaged in airline industry, and Pertamina is a non service company engaged in oil and gas industry.Using factor analysis and multiple regression, the result indicates some differences between firms CSR activities in in developing children well being and customer loyalty. This result has implication for the firm that different type of CSR activities and different industry will reflect different motives, further have different impact in children’s well being.